Relationship of grit and resilience to dental students' academic success. Issue 2 (23rd September 2020) - Montas, Mackenson; Rao, Sowmya R.; Atassi, Hamza Al; Shapiro, Michael C.; Dean, Jason; Salama, Andrew R.
Abstract: Objectives: This study assesses the levels of grit (the perseverance and passion for long‐term goals), and resilience (the ability to bounce back or recover from stress), reported by U.S. dental students, and its possible association with academic achievements. Methods: An anonymous 27 question cross‐sectional online survey with sections on demographics, grit, resilience, and academic achievement was e‐mailed to all dental students in the U.S. The Short Grit and Brief Resilience scales were used. Scores for both scales ranged from 1 to 5, and were grouped into low, moderate, and high tertiles based on distribution. Dental school grade point average (GPA), and class rank were used to measure academic achievement, and were similarly grouped. Odds ratios (ORs) and 95% confidence intervals (CIs) were obtained from multinomial logistic regression models assessing the relationship of grit and resilience to the outcomes adjusting for gender, dental school year, race, geographic origin, and a variable combining education and income. Results: Of the 3292 (17%) respondents, 58% were female. Hispanics reported significantly higher grit and resilience scores while Asian students reported the lowest. 18% of Hispanics were ranked in the top 20 percentile versus 37% of whites. Conclusion: Results indicate that dental students with high grit (high vs. low scores: OR [95% CI]: 2.06 [1.57–2.72]) and resilience (high vs. low scores: 1.36 [1.04–1.76]) achieved higher GPA and better class ranks. Therefore, it is crucial for students wanting to achieve academic success to consider the value that these non‐cognitive characteristics might have on their overall progress.